The effect of different retraining intervals on the skill performance of cardiopulmonary resuscitation in laypeople—A three-armed randomized control study. (July 2018) - Hsieh, Ming-Ju; Chiang, Wen-Chu; Jan, Chyi-Feng; Lin, Hao-Yang; Yang, Chih-Wei; Ma, Matthew Huei-Ming
Abstract: Aim: Our study aimed to compare cardiopulmonary resuscitation (CPR) performance among laypeople with different retraining intervals. Methods: Ninety-six non-medical university students were randomly allocated into 3 groups after receiving initial CPR and automated external defibrillator (AED) training. Sixty participants completed the study. The participants in the 3-, 6-, and 12-month groups received the same retraining every 3-, 6-, and 12 months. An 80-min retraining course comprised a video lecture and hands-on practice, with feedback from the instructors and the Resusci Anne ® QCPR. The primary outcome was a skill pass rate one year post-initial training. The secondary outcomes included a skill pass rate prior to each retraining course, knowledge test scores, and individual skill performance evaluated by assessors and by SkillReporter ® software one year post-initial training. Results: The characteristics among the groups were similar. The 3-month group had the highest pass rate (3-month group: 6-month group: 12-month group, 100.0%: 78.9%: 19.0%, p  < 0.001) in the primary outcome. In secondary outcomes, the 3-month group had a higher pass rate than the 6-month group at 6 months post-initial training. The 3-month group achieved the highest knowledge test scores, and performed best in many ventilation items. They showed similar performance to the 6-month group and better performance than the 12-month group in chest compression items. The 3 groups performed similarly in AED manipulation. Conclusions: Although young laypeople with a 3-month retraining interval had the highest pass rate when performing conventional CPR, a 6-month retraining interval may be considered for training compression-only CPR and AED when balancing outcomes and resources.